Basic electrocardiography : normal and abnormal ECG patterns - Bayés de Luna, Antoni, 1936- (John Wiley & Sons, 2008)
Electrocardiography is a simple investigation to perform, but accurate interpretation can be challenging. This book takes a logical and systematic approach to ECG interpretation, beginning with the basics of normal variations and dealing in turn with atrial abnormalities, ventricular enlargement, ventricular conduction defects and ischemic heart disease. Extensively illustrated with ECG tracings that complement the text, this book provides clear and concise explanations of traditional concepts of electrocardiography and combines them with updates on the most recent developments in the field. I.